Catatonic Episodes Related to Substance Use: A Cross-Sectional Study Using Electronic Healthcare Records. Issue 1 (2nd January 2022) - Yeoh, Su Ying; Roberts, Emmert; Scott, Fraser; Nicholson, Timothy R.; David, Anthony S.; Rogers, Jonathan P.
Abstract: Objective: Substance use has increasingly been linked to the onset of catatonic episodes; however, no large observational studies have examined this association. This study aimed to identify catatonic episodes temporally associated with acute intoxication, withdrawal or chronic substance use, investigate which substances were involved, and compare clinical characteristics of substance-related and non-substance-related catatonic episodes. Methods: This study retrospectively identified all catatonic episodes recorded in an electronic case register hosted at a large secondary mental health trust in London, UK. Episodes were categorized as substance-related if the clinical record reported either a positive urine drug screen, an ICD-10 diagnosis of a mental or behavioral disorder due to substance use, or documented substance use between two weeks prior to the catatonic episode and the date of the catatonic episode. Results: 108 of 2130 catatonic episodes (5.1%) were deemed substance-related. The number of contemporaneously reported substance-related episodes increased between 2007 and 2016 [ r  = 0.72, p  = 0.02]. Episodes in the context of acute intoxication ( n  = 54) were most frequently related to cannabis ( n  = 31) or cocaine ( n  = 5) use, whilst those in the context of drug withdrawal ( n  = 8) were most commonly related to alcohol, opioids and benzodiazepines. There were 50 episodes of catatonia associated with chronic substance use without intoxication or withdrawal, of which the majority were related to cannabis use ( n  = 37). 21 episodes had overlapping intoxication, withdrawal and chronic use of different substances within an episode. Compared to catatonic episodes not related to substance use, episodes of substance-related catatonia occurred in individuals who were younger (mean age 31.3 years [SD 12.2] vs 35.7 years [SD 16.3], p  = 0.01) and more likely to be men (74.0% vs 54.3%, p  < 0.001). The clinical features of catatonia were similar between the two groups. Conclusions: A relatively small proportion of catatonic episodes were temporally associated with reported substance use within their electronic records. Substance-related catatonic episodes were mostly related to cannabis use, but other substances including cocaine, alcohol, opioids and benzodiazepines were sometimes implicated. This is likely an underestimate of substance-related catatonia use due to issues with documentation and appropriate investigation.